PERAN KOMUNIKASI INTERPERSONAL IBU DAN ANAK USIA SEKOLAH DASAR SEBAGAI UPAYA MEMBENTUK RESILIENSI DIRI PADA MASA PANDEMI COVID-19 DI PERUMAHAN SC RESIDENCE KABUPATEN GARUT - Mochamad Sulthan Arabella Djafar (2022)
This study aims to understand the role of mother and child interpersonal communication as an effort to form self-resilience during the COVID-19 pandemic, especially in the Garut Regency area, as well as to strengthen knowledge about the application of mother and child interpersonal communication theory as an effort to form self-resilience during the COVID-19 pandemic. 19 in depth. The researcher used this type of qualitative research with a descriptive approach. The data collection technique used in-depth interviews with five informants. The data analysis technique used by the researcher is the analysis technique according to Miles and Hubberman which consists of three stages, namely data reduction, data display, and drawing conclusions. The final result of this study shows that the role of interpersonal communication that mothers do to elementary school age children is by means of verbal communication by providing understanding and knowledge about the dangers of the COVID-19 virus and the importance of complying with health protocols. Broadly speaking, the interpersonal communication that mothers do to elementary school-aged children has a good effect and change. In addition, the visible effect is the child's immune system becomes stronger. The changes seen in children are that children become aware of health protocols wherever they are, this is different when before the COVID-19 virus pandemic appeared because previously children did not pay attention to their own hygiene and health. Broadly speaking, the role of interpersonal communication between mothers and elementary school-aged children is quite effective in shaping self-resilience during the current COVID-19 pandemic.